Social networks and women micro-enterprise performance: a conceptual framework - Isidore Ekpe; Norsiah Mat; Margaret Isidore Ekpe (2015)
This study aims at examining the impact of social networks on women micro-enterprise’s performance in Malaysia. This is to compare the situation in Malaysia with other countries, as to whether scarcity of studies exist in this area, and whether similar results obtained globally could be established in Malaysia, given her multi-racial and ethnic diversity. The result of this study will help women entrepreneurs increase their business performance, enable the government assess the effectiveness of her micro-enterprise assistance programs and develop strategies to enhance the ability of women entrepreneurs to benefit from their social networks in order to improve their business performance; in line with global practice. The study uses a cross-sectional survey design, with stratified random sampling, to collect data from women entrepreneurs in Malaysia Peninsula. The study also uses t-test to determine whether the success or failure of women micro-enterprises was due to availability or lack of social networks. Therefore, it samples two groups made up of well-established women clients and nascent women clients of a microfinance bank. Descriptive statistics and hierarchical regression are data analyses methods. The study concludes that women entrepreneurs do not only need loans and skill acquisition training but also social networks to provide access to information and other resources such as professional advice and avenue for customers. It is recommended that the government should create awareness among the women about the existence and benefits of women associations and groups, especially in local areas since most of such associations are located in urban cities.